Knowledge engineering and knowledge management : EKAW 2016 Satellite Events, EKM and Drift-an-LOD, Bologna, Italy, November 19-23, 2016, Revised selected papers /: EKAW 2016 Satellite Events, EKM and Drift-an-LOD, Bologna, Italy, November 19-23, 2016, Revised selected papers. (2017) - Unknown
No abstract available